Urban Diabetic Women’s Perception of Healthy Eating Lifestyles from West Java - Mayumi Mizutani; Junko Tashiro; Nia Damiati; Uswatun Khasanah (JKP (Jurnal Keperawatan Padjajaran), 2015)
This study aimed to explore perceptions about a healthy-eating lifestyle and reasons to practice a healthy-eating lifestyle of women with type 2 diabetes in a city of West Java by using a case study design. Six female patients, with type 2 diabetes, ages 47-63 from a hospital were interviewed guided by the health promotion model. Their healthy-eating lifestyle included currently practicing or not practicing a healthy-eating lifestyle. Reasons to practice were: beliefs for health and for physical energy to work for family, definition of multidimensional health and self-efficacy increased by: support from God, support from family, support from health professionals and improved or deteriorated health status by prior experience. Reasons not to practice were: difficulty in arranging diet, rejecting eating, controlling appetite, and accessing health care services. Related difficulties were interpersonal relations with family and social situation such as social events, expensive medical fee, and distance to the hospital. These findings suggest that women with type 2 diabetes in Indonesia need to be supported with the reasons to practice a healthy-eating lifestyle.